A Review of Digital Data Resources on Innovation and Impact - Sartas, Murat; Zervas, P.; Sotiris, P.; Sarfatti, P.; Schut, Marc; Bonaiuti, Enrico; Clarke, V.; Negroustoueva, S. (2021)
The CGIAR Research Program on Roots, Tubers, and Bananas (RTB) has commissioned a study to develop an innovation catalog to present its innovation portfolio to the international scientific and development community and to support ongoing efforts to establish an innovation management architecture in CGIAR. The study team has been tasked with designing an application model that can inform the innovation and impact management architecture of CGIAR and test it within the RTB innovation portfolio leading to an RTB Innovation Catalog that can be used as an example for future work. Guided by the recently finalized work methodology, the interdisciplinary research and technical team members have reviewed existing digital resources, i.e. web portals and databases that present the social innovations across multiple sectors such as agriculture, food, environment, health, and energy to the international research-for-development and impact investment communities. This document describes the methods and the findings of this review. It shows the profiles, features, and data provided by the digital resources; compares and contrasts them by assessing their relevance, effectiveness, efficiency, functionality, and formats. It shows that, although there are a few features that most existing digital resourcesshare, i.e. being hosted by international organizations, having easy to-navigate interfaces, and providing limited filtering and search options, there are significant differences between them. The digital resources focus on different subsets of innovation-related information and provide different levels of granularity. The review concludes that to present its innovations across the broad spectrum of digital resources, the RTB Program and CGIAR need to use rich metadata sets with a few different interface and export options to be customized based on the profile of individual, essential digital resources of interest.